Business Unit Strategy and Changes in the Product R&D Budget - Hambrick, Donald C.; MacMillan, Ian C.; Barbosa, Ricardo R. (Management Science, 1983)
This study of changes in Product R&D intensity in business units supplements past studies by including two major classes of independent variables which have not been examined previously: the competitive strategy of the business and role of the business in the overall corporate portfolio. Multiple regression analysis is used on a sample drawn from the PIMS data base. The results suggest that R&D decisions in growth businesses are responsive to competition, evolving strategies, and intra-firm resource flows. In mature businesses, a pattern of stability and R&D equilibrium is evident, even in the face of changes by competitors. Managerial implications are noted.